Basic Concepts and Values of Mathematics in Bengkulu Traditional Musical Instruments as Media and Resources for Learning Mathematics - Haji, Saleh; Yumiati, Yumiati; Zamzaili, Zamzaili (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine the basic concepts and values of mathematics contained in traditional Bengkulu musical instruments in elementary schools. The urgency of this research is to use regional culture in learning mathematics theoretically and practically as a medium and source of learning mathematics through learning outside the classroom to achieve the objectives of learning mathematics in elementary schools. This research method is a qualitative method with an ethnographic approach. Data sources are in the form of traditional Bengkulu musical instruments, namely dhol, tassa, long drums, and serunai. Other data sources are documents and interviews with experts and practitioners of Bengkulu traditional musical instruments. The data were analyzed qualitatively with the method of content analysis. The result of this study shows that the basic mathematical concepts in Bengkulu traditional musical instruments are points, lines, angles, triangles, quadrilaterals, kites, circles, tubes, half balls, cut balls, cut cones, universes, and patterns. At the same time, the mathematical values contained in traditional Bengkulu musical instruments are obeying the rules, consistency, creativity, and cooperation. Therefore, as an alternative to effective learning in elementary schools, Bengkulu traditional musical instruments can be used as a medium and source of learning mathematics outside the classroom.